“Cues” for Non-Routine Decisions on the Fireground - M. Khalid Shaikh (Journal of Basic & Applied Sciences, 2016)
A decision making model for building decision support system is reported here that is developed through working with fireground incident commanders of the United Kingdom. The model is suitable for decision making in non-routine situations. A detailed description of the development of the model is available in Shaikh (2011). There is a need to develop a working prototype decision support systems based on this model particularly for training and helping FGCs working in countries such as Pakistan, Sri Lanka, Indonesia etc. Editorial